EFEK MODERASI LAMA BERLANGGANAN PADA HUBUNGAN ANTARA KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN - Dewi, Liana; Fauzi, Willy Muhammad; Rakista, Putri Mutiara; Hadi, Dadih Abdul; Kusumah, Danial (FAKULTAS VOKASI UNIVERSITAS MAYASARI BAKTI, 2024)
The moderating effect of subscription length on the relationship between service quality and customer satisfaction. Customer satisfaction is a benchmark for an institution's ability to provide services to the community. Customer satisfaction for drinking water companies is something they strive for. Equal distribution of services is one of the things that can contribute to customer satisfaction. This research aims to examine the relationship between service quality and customer satisfaction, moderated by length of subscription. The population in this study were customers of Perumda Air Minum Tirta Sukapura, Tasikmalaya Regency. The sample size was determined according to the Kjercie and Morgan model. The sample was determined using proportionate random sampling technique where the number of samples for each region was adjusted to the population size. The test results show that there is a close relationship between service quality and customer satisfaction. Length of subscription cannot moderate the relationship between service quality and customer satisfaction.